2017
DOI: 10.4238/gmr16019409
|View full text |Cite
|
Sign up to set email alerts
|

Myrciaria dubia, an Amazonian fruit: population structure and its implications for germplasm conservation and genetic improvement

Abstract: ABSTRACT. Myrciaria dubia (camu-camu) is an Amazon tree that produces a tart fruit with high vitamin C content. It is probably the fruit with the highest vitamin C content among all Brazilian fruit crops and it can be used to supplement daily vitamin C dose. This property has attracted the attention of consumers and, consequently, encouraged fruit farmers to produce it. In order to identify and select potential accessions for commercial exploitation and breeding programs, M. dubia has received considerable res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The inter-and intra-population genetic variability was similar to that found by Nunes et al (2017) when analyzing 10 populations of M. dubia from Dos Reis lake, in Roraima, finding greater variability within (65%) than among populations (35%), with the use of 14 ISSR markers. The distribution patterns of genetic variability are highly correlated with the reproductive systems of plants (Martins, 1987).…”
Section: Discussionsupporting
confidence: 75%
“…The inter-and intra-population genetic variability was similar to that found by Nunes et al (2017) when analyzing 10 populations of M. dubia from Dos Reis lake, in Roraima, finding greater variability within (65%) than among populations (35%), with the use of 14 ISSR markers. The distribution patterns of genetic variability are highly correlated with the reproductive systems of plants (Martins, 1987).…”
Section: Discussionsupporting
confidence: 75%
“…At that time, the presence of genetic structure was demonstrated among populations (two genetic groups) with an average heterozygosity of 0.08-0.14. Subsequent studies have analyzed the genetic diversity in germplasm collections and cultured populations using DNA markers, such as rapid amplification of polymorphic DNA (RAPD) [45], inter simple sequence repeat (ISSR) [8], expressed sequences tag-simple sequence repeats (EST-SSR) [9,46,47], and SSR [10,11], also known as microsatellite markers. Overall, these investigations found that the average expected heterozygosity (He = 0.67 AE 0.19, range of 0.45-0.88) was greater than the average observed heterozygosity Likewise, the average intrapopulation genetic diversity (average 74.89%, range of 65-79%) is $3 times greater than average interpopulation genetic diversity (average 25.10%, range of 20-35%).…”
Section: Genetic Diversitymentioning
confidence: 99%
“…This plant species possesses a diploid genome, and their genome size (230 Mb) is in the range of other Myrtaceae species [3][4][5][6]. Populations exhibit moderate genetic diversity and genetic structuring [7][8][9][10][11]. Camu camu produces several essential nutrients such as amino acids, polyunsaturated fatty acids, B-complex vitamins, and high quantities of vitamin C [2,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Germplasm collections with specimens from all the Amazon basin are active in Brazil at INPA (Instituto Nacional de Pesquisa da Amazônia) and EMBRAPA, with ex-situ collections in Manaus, Belem and Boa Vista (Nascimento et al, 2013;Sakazaki et al, 2022;Yuyama & Valente, 2011), and in Peru at IIAP (Instituto de Investigaciones de la Amazonía Peruana) from western Amazonia (Pinedo-Panduro et al, 2020;Šmíd et al, 2017). Genetic studies have shown a high intra-and inter-population variability with a high geographic structure (Nunes et al, 2017, Rojas et al, 2011Šmíd et al, 2017;Souza et al, 2020), which indicates that to conserve the existing genetic diversity it will be needed to sample at large geographic scales.…”
Section: Introductionmentioning
confidence: 99%